Seroprevalence of Brucellosis in Cattle of Rupandehi District, Nepal - Chalise, S.; Pandeya, Y. (NPI Journal of Science and Technology, 2024)
Brucellosis is a contagious zoonotic disease affecting both cattle and humans, with notable economic and public health implications in Nepal. Despite previous studies indicating varying prevalence rates in different regions of the country, there is limited recent data on the status of Brucellosis in Rupandehi district. A cross-sectional study was conducted in Rupandehi district, Nepal, from 1st July to 30th September 2023. A total of 141 cattle blood samples from 92 farms were collected and tested using ID Screen® Brucellosis Indirect ELISA kits. Epidemiological survey was also conducted to gather information on risk factors associated with Brucellosis. All 141 blood samples were tested negative for Brucellosis, resulting in a seroprevalence rate of 0%. This study provides valuable data indicating a zero prevalence of Brucellosis in cattle of Rupandehi district, Nepal. This research doesn’t show any association for the prevalence of Brucellosis regarding the risk factor.